2018
DOI: 10.1039/c8dt03780a
|View full text |Cite
|
Sign up to set email alerts
|

Copper(ii) complexes for cysteine detection using 19F magnetic resonance

Abstract: Cysteine plays an essential role in maintaining cellular redox homeostasis and perturbations in cysteine concentration are associated with cardiovascular disease, liver disease, and cancer. 19F MRI is a promising modality for detecting cysteine in biology due to its high tissue penetration and negligible biological background signal. Herein we report fluorinated macrocyclic copper complexes that display a 19F NMR/MRI turn-on response following reduction of the Cu(II) complexes by cysteine. The reactivity with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…[14][15][16][17][18][19][20] Due to the instability of PFCe mulsions, [21,22] encapsulating PFCs into alginatec apsuleso rs ilica nanoparticles has recently been pursued. [23][24][25][26][27] Lastly,h ypoxia-responsive 19 F probesu tilizing paramagnetic relaxation enhancement (PRE) have been shown to accumulate selectively in hypoxic cells, [28][29][30][31] but the low loading of 19 Fn uclei limits their sensitivity.…”
mentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Due to the instability of PFCe mulsions, [21,22] encapsulating PFCs into alginatec apsuleso rs ilica nanoparticles has recently been pursued. [23][24][25][26][27] Lastly,h ypoxia-responsive 19 F probesu tilizing paramagnetic relaxation enhancement (PRE) have been shown to accumulate selectively in hypoxic cells, [28][29][30][31] but the low loading of 19 Fn uclei limits their sensitivity.…”
mentioning
confidence: 99%
“…Thus it was decided to promote a modification on the electrode surface by electrodepositing CuNP, since the interaction between this metal and Cys is known and largely studied in the literature. 34,38,40,41 After CuNP electrodeposition, cyclic voltammograms obtained in the presence of 1.0 mmol L -1 Cys in 0.10 mol L -1 phosphate buffer pH 7.0 demonstrated that although copper oxidation and reduction took place, no significant changes in current intensities were observed. Furthermore, an additional treatment in basic media of the modified electrode was proposed in order to generate a mixture of active copper oxide sites on the metallic layer.…”
Section: Cysteine Redox Behavior At Gpue and Gpue-cunpmentioning
confidence: 98%
“…Similar phenomenon occurred in the reduction peak, while it was displaced to more negative potentials. This might be related to the Cys interaction with Cu + ions 34,40 onto the treated GPUE-CuNP surface, due to the formation of a stable and soluble Cys-Cu + complex. This phenomenon has already been described in the literature 34,38,40 and should occur according to equation 4: its occurrence is corroborated by the displacement of the reduction peak towards more negative potentials.…”
Section: Cysteine Redox Behavior At Gpue and Gpue-cunpmentioning
confidence: 99%
See 1 more Smart Citation
“…Paramagnetic metals can be used to modulate both 19 F andfluorescence signal to make biosensors. [30][31][32][33][34][35][36][37][38][39] To develop bimodal hypoxia-responsive probes for 19 F MRI and fluorescence, we chose the CuATSM scaffold as the paramagnetic Cu 2+ center will quench both the 19 F MR signal via paramagnetic relaxation enhancement (PRE) 7,8 and the fluorescence signal due to electron transfer from the excited fluorophore to the paramagnetic metal center (Scheme 1). 36 Following reduction to Cu + and ligand dissociation, both of these effects will be relieved, resulting in signal turn-on in both modalities.…”
mentioning
confidence: 99%